2017
DOI: 10.7860/jcdr/2017/24573.9209
|View full text |Cite
|
Sign up to set email alerts
|

Visible Evidence of Lumbar Epidural Catheter Misplacement–A Critical Incident Case Report

Abstract: A 57-year-old, male patient (165 cm, 66 kg) was scheduled to undergo right radical nephrectomy for renal cell carcinoma. Clinical history, physical examinations and laboratory investigations of the patient were normal. After placing the patient in right lateral position, epidural space was identified at first attempt with 18G Tuohy needle (BD Perisafe, Belgium) via a midline approach at L2-L3 intervertebral space using loss of resistance to air technique. A 20G multiorifice epidural catheter was threaded throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…As shown, the contrast was injected via the catheter, and a CT scan was performed, which revealed contrast uptake in the psoas major muscle [ 13 ]. The other report [ 14 ] affirms direct visualization of the catheter tip in the psoas muscle during radical nephrectomy of a preoperatively placed lumbar epidural catheter. In the first report [ 13 ], the authors highlighted the fact that there is effective analgesia when the bolus is administered, and analgesia failure only manifests on continuous fixed-rate infusion with DIB.…”
Section: Discussionmentioning
confidence: 76%
“…As shown, the contrast was injected via the catheter, and a CT scan was performed, which revealed contrast uptake in the psoas major muscle [ 13 ]. The other report [ 14 ] affirms direct visualization of the catheter tip in the psoas muscle during radical nephrectomy of a preoperatively placed lumbar epidural catheter. In the first report [ 13 ], the authors highlighted the fact that there is effective analgesia when the bolus is administered, and analgesia failure only manifests on continuous fixed-rate infusion with DIB.…”
Section: Discussionmentioning
confidence: 76%
“…[ 2 3 ] A misplaced catheter from the thoracic paravertebral space into the epidural space can be confirmed by postoperative radiograph, and a lumbar epidural catheter was detected in the psoas major muscle during an open nephrectomy. [ 4 5 ] However, in our case, epidural catheter inadvertently entered the lumbar paravertebral space during an attempted lumbar epidural in a patient with severe lumbar scoliosis.…”
mentioning
confidence: 76%
“…Lumbar epidural catheter misplacement is seldom recognized during surgery. Rajira et al [7] reported a case of right-sided open nephrectomy, in which the catheter was found in the surgical field emerging from the psoas major muscle.…”
Section: Discussionmentioning
confidence: 99%